Temperature Distribution and Combustion Characteristics of Rice Husks in a Fluidized Bed Combustor - Manop, Chalermchat; Wongcharee, Khwanchit; Chuwattanakul, Varesa; Promvonge, Pongjet; Saysroy, Anucha; Eiamsa-Ard, Smith (My University, 2022)
This article presents an experimental study on the combustion characteristics of rice husks in a fluidized bed combustor (FBC). In the experiments, the FBC was tested with rice husk feeding rates ranging from 10-15.5 kg/hr to yield percent excess air (EA) between 25% and 35%. The axial and radial temperature distribution within the FBC was measured at a selected location while gas emissions were also monitored. From the experimental results, it can be seen that the maximum exhaust gas temperature is between 852 and 950 °C. In the exhaust gas emission analysis, CO is in the range of 951-1452 ppm, NO between 271 ppm and 303 ppm, CO2 between 6.5% and 9.5%, and O2 between 5.1% and 12.8%.